Ketentuan Pakaian Perempuan Menurut Fikih dan Qanun Aceh - Muhammad Haikal; Azmi Abubakar (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
Women are creatures that almost all of their bodies are naked. Aurat must be covered. Covering the genitals is called clothing. This study looks at the provisions of clothing according to fiqh and Aceh qanuns. The research method is qualitative by tracing the fiqh literature and the text of the 2002 Aceh qanun. The results show that sharia does not limit the model and type of clothing to cover the genitals, but limits the conditions that must be met, as well as in the qanun. There is a correlation between fiqh and qanun for the implementation of Islamic law in the fields of faith and worship.